PENGARUH BRAND IMAGE DAN ELECTRONIC WORD OF MOUTH TERHADAP MINAT BELI KONSUMEN MIXUE DI TROPODO - Saragih, Yolanda; Yuliati, Nuriah; Laily, Dona Wahyuning (MEDIAGRO, 2023)
Competition in the food and beverage industry in Indonesia is currently increasingly competitive. The growth of the food and beverage industry will reach 3.57% in 2022. One of the growing retail businesses in Indonesia is engaged in the food and beverage industry, namely Mixue Ice Cream and Tea, which manages soft-serve ice cream and tea drinks, but several months recently, this company has experienced an increase in complaints or negative comments by consumers. This study aims to analyze the effect of brand image and electronic word of mouth on Mixue Ice Cream and Tea beverage products. This research was conducted at the Tropodo branch of Mixue Ice Cream and Tea. The sampling technique used purposive sampling with a total sample of 55 people. Methods of data analysis using descriptive analysis and SEM-PLS analysis with the SmartPLS version 4 application. Based on the analysis it is known that the Brand Image and Electronic Word of Mouth variables significantly influence the Interest to Buy Mixue Ice Cream and Tea, because it has a p-value of 0.000 < 0.05. Keywords: Brand Image, Electronic Word of Mouth, Buying Interest, SEM-PLS